Numerical study of the coupled time-dependent Gross-Pitaevskii equation: Application to Bose-Einstein condensation - Adhikari, S. K. [UNESP] (American Physical Society (APS), 2001)
The Bose-Einstein condensate of several types of trapped bosons at ultralow temperature was described using the coupled time dependent Gross-Pitaevskii equation. Both the stationary and time evolution problems were analyzed using this approach. The ground state stationary wave functions were found to be sharply peaked near the origin for attractive interatomic interaction for larger nonlinearity while for a repulsive interatomic interaction the wave function extends over a larger region of space.
Keywords: Atomic physics; Boundary conditions; Lattice vibrations; Low temperature effects; Mathematical models; Oscillations; Quantum electronics; Bose-Einstein condensation (BEC); Gross-Pitaevskii equation; Condensation